Detection and quantification of Melissococcus plutonius in honey bee workers exposed to European foulbrood in Czechia through conventional PCR, qPCR, and barcode sequencing. Issue 4 (7th August 2020) - Sopko, Bruno; Zitek, Justyna; Nesvorna, Marta; Markovic, Martin; Kamler, Martin; Titera, Dalibor; Erban, Tomas; Hubert, Jan
Abstract : Melissococcus plutonius is the causative agent of European foulbrood (EFB), an important bacterial disease of honey bee larvae, and various methods have been developed for the detection of this disease. Adult bees are not affected but spread M. plutonius among beehives and serve as a diagnostic tool to detect EFB. Melissococcus plutonius detection based on conventional polymerase chain reaction (PCR) (16S DNA), qPCR (sodA), and barcode sequencing of the 16S RNA V4 region in worker bees from colonies with and without clinical symptoms were compared. We validated these detection tools in terms of the presence/absence of clinical signs of the disease. The comparison of the PCR- and qPCR-based methods showed their usability for confirmation of the disease in both colonies with and without clinical symptoms. Our results revealed that qPCR was more suitable for the confirmation of clinical EFB than conventional PCR and that conventional PCR was better for general screening, including the screening of asymptomatic colonies, than qPCR. Redundancy analyses (tbRDAs) of the microbiome composition showed that the detection limit-based qPCR of M. plutonius revealed a greater variability in the microbiome profiles of worker bees compared with that explained by clinical signs of the disease and PCR detection as factors. The presence of "secondary invaders" ( Paenibacillus alvei and Enterococcus ) was positively correlated with an increase in the profile of M. plutonius in the worker bee microbiome, whereas Apibacter adventoris and Bartonella apis were negatively correlated. Both types of correlations were found among Lactobacilli.